COMBINING EFFECTS OF CULTURAL PRACTICES AND RESISTANT CULTIVARS ON REDUCING THE INCIDENCE OF Meloidogyne spp. AND Thrips palmy Karny ON POTATO - Setiawati, Wiwin; Karjadi, Asih Kartasih; Soetiarso, Thomas Agoes (Indonesian Agency for Agricultural Research and Development - MOA, 2010)
Root-knot nematode (Meloidogyne spp.) and melon thrips(Thrips palmy Karny) are two serious pests on potato. Thesepests are conventionally controlled with synthetic pesticides.Cultural practices based on integrated pest management (IPM)are alternative methods to control these pests. The study aimedto determine the effectiveness of combined applications ofcultural practices and potato cultivars in reducing the incidencesof nematode and thrips. Treatments evaluated were methods ofnematode and thrips control by implementing IPM and conventionalpractices. A split-plot randomized complete block designwith four replications was used. The main plots were IPM orcultural practices (subsoiling, soil solarization and use of trapcrop of marigold Tagetes erecta) and conventional practicesusing synthetic pesticides. The subplots were five potato cultivars,i.e. No. 095 (Herta x FLSâ17), 720050/Kikondo, 676068/I.1085, Granola, and Atlantic. The results showed that applicationsof cultural practices in combination with potato cultivarsreduced Meloidogyne spp. population and potato tuber damageby 53.70% and 61.36%, respectively, as well as a significantlydecreased thrips population. In the cultural control plots, thripspopulations were below the action threshold (10.0 nymphs perleaf), therefore no single application of pesticide was used. Thiswas in contrast to the conventional control treatments whereinsecticide was spayed 10 times until harvest. The subsoiling andsolarization cut off the life cycle of the thrips and any survivethrips were trapped by marigold plant. Population of T. palmion the five potato cultivars differed significantly; the lowestpopulation was found on the cultivars No. 095 (Herta x FLS-17)and 676068/I.1085. The cultural control practices combinedwith potato cultivar No. 095 (Herta x FLSâ17) were the besttreatment for controlling Meloidogyne spp. and T. palmi onpotato and also produced the highest yield (31.01 t ha-1). Thestudy suggests that cultural control practices in combination withresistant cultivars are recommended as a suitable IPM to controlnematode and thrips on potato crops.